Multiple methods of diet assessment reveal differences in Atlantic puffin diet between ages, breeding stages, and years - William L. Kennerley; Gemma V. Clucas; Donald E. Lyons; Donald E. Lyons (Frontiers in Marine Science, 2024)
IntroductionAtlantic puffin (Fratercula arctica, hereafter “puffin”) reproductive success in the Gulf of Maine (GoM) has declined following a recent oceanographic regime shift that has led to rapid warming and increasingly frequent marine heatwaves. Concurrent changes in both the regional forage fish community and puffin chick diets and provisioning rates suggest that inadequate prey resources may be driving this decline. Traditional, noninvasive methods of diet assessment, however, are unable to determine seabird diet at many age classes and breeding stages.MethodsTo determine what prey GoM puffins were feeding on during two years of marine heatwave conditions, we assessed puffin diet using two complementary methods: traditional, observational methods that utilize bill-load photography and emerging methods employing fecal DNA metabarcoding. We then examined the effect of methodology, age, breeding stage, and year on puffin diet composition. ResultsWe identified a strong correlation between the composition of chick diet as estimated through traditional and emerging methods, supporting the interpretation of DNA relative read abundance as a quantitative metric of diet composition. Both methods identified the same dominant prey groups yet metabarcoding identified a greater number of species and offered higher taxonomic resolution. Additionally, metabarcoding revealed adult puffin diet during the incubation period for the first time. Although puffin adults and chicks fed on many of the same prey types, adults consumed a greater variety of taxa and consumed more low quality prey types than they provisioned chicks.DiscussionFor both age classes, diet varied both between and within years, likely reflecting changes in the local forage fish community in response to environmental variability. Puffins exploited unusual abundances of typically-uncommon prey during these two years of marine heatwave conditions, yet low puffin productivity suggests the observed dietary plasticity was not fully able to compensate for apparent prey shortages. Continued refinement of molecular methods and the interpretation of the data they provide will enable better assessments of how seabirds of diverse ages and breeding stages are adapting to changing prey communities.